Drain Versus No Drain in Lichtenstein Hernioplasty for Complete Inguinal Hernia: A Comparative Study - Abineshwar, N. J.; R, Arunkumar; Rajasekaran, C.; Avinash, Yeleti. Subha; Sridhar, J. (Journal of Neonatal Surgery, 2025)
Background: Inguinal hernia is a prevalent surgical condition worldwide, necessitating surgical repair for effective management. Lichtenstein hernioplasty, a tension-free mesh repair technique, is widely adopted due to its low recurrence rates. However, the role of drains in this procedure remains controversial. While some surgeons advocate for the use of drains to prevent seroma and hematoma formation, others argue that drains may increase the risk of infection and prolong hospital stay. This study evaluates the comparative efficacy of using a drain versus no drain in Lichtenstein hernioplasty for complete inguinal hernia repair. Objectives: The primary objective of this study is to compare the postoperative outcomes between patients undergoing Lichtenstein hernioplasty with and without the use of a drain. Specific outcomes assessed include surgical site infection, seroma formation, postoperative pain, and hospital stay duration. Methods:This hospital-based prospective randomized controlled trial was conducted over ten months, enrolling 106 patients diagnosed with complete inguinal hernia and scheduled for elective Lichtenstein hernioplasty. Patients were randomized into two equal groups: one undergoing hernioplasty with a drain (n=53) and the other without a drain (n=53). Perioperative and postoperative parameters were documented, including operative time, incidence of seroma and hematoma formation, postoperative pain assessed via the Visual Analog Scale (VAS), surgical site infections, and hospital stay duration. Data were analyzed using SPSS v22, with a significance threshold set at p<0.05. Results: The mean operative time was longer in the drain group compared to the no-drain group (p<0.05). Seroma formation was observed in 39.1% of patients in the drain group and 60.9% in the no-drain group. However, hematoma formation was more common in the no-drain group (62.5% vs. 37.5%). Surgical site infection was more prevalent in the drain group (57.4%) compared to the no-drain group (42.6%). The mean postoperative pain scores were significantly higher in the drain group in the initial postoperative days (p<0.001). The hospital stay was prolonged in patients with drains, with fewer patients in this group being discharged within three days compared to those without drains (p<0.001). Conclusion:The findings indicate that the use of drains in Lichtenstein hernioplasty does not provide significant advantages in preventing postoperative complications. Instead, it is associated with increased postoperative pain, higher infection rates, and prolonged hospital stay. Routine drain placement should be reconsidered and reserved for selected cases with extensive dissection or high-risk factors for fluid accumulation.